Markers of anti-malarial drug resistance in Plasmodium falciparum isolates from Swaziland: identification of pfmdr1-86F in natural parasite isolates - Beshir Khalid; Dlamini Sabelo V; Sutherland Colin J (Malaria Journal, 2010)
Abstract Background The development of Plasmodium falciparum resistance to chloroquine (CQ) has limited its use in many malaria endemic areas of the world. However, despite recent drug policy changes to adopt the more effective artemisinin-based combination (ACT) in Africa and in the Southern African region, in 2007 Swaziland still relied on CQ as first-line anti-malarial drug. Methods Parasite DNA was amplified from P. falciparum isolates from Swaziland collected in 1999 (thick smear blood slides) and 2007 (filter paper blood spots). Markers of CQ and sulphadoxine-pyrimethamine (SP) resistance were identified by probe-based qPCR and DNA sequencing. Results Retrospective microscopy, confirmed by PCR amplification, found that only six of 252 patients treated for uncomplicated malaria in 2007 carried detectable P. falciparum. The pfcrt haplotype 72C/73V/74I/75E/76T occurred at a prevalence of 70% (n = 64) in 1999 and 83% (n = 6) in 2007. Prevalence of the pfmdr1-86N allele was 24% in 1999 and 67% in 2007. A novel substitution of phenylalanine for asparagine at codon 86 of pfmdr1 (N86F) occurred in two of 51 isolates successfully amplified from 1999. The pfmdr1-1246Y allele was common in 1999, with a prevalence of 49%, but was absent among isolates collected in 2007. The 86N/184F/1246D pfmdr1 haplotype, associated with enhanced parasite survival in patients treated with artemether-lumefantrine, comprised 8% of 1999 isolates, and 67% among 2007 isolates. The pfdhfr triple-mutant 16C/51I/59R/108N/164I haplotype associated with pyrimethamine resistance was common in both 1999 (82%, n = 34) and 2007 (50%, n = 6), as was the wild-type 431I/436S/437A/540K/581A/613A haplotype of pfdhps (100% and 93% respectively in 1999 and 2007). The quintuple-mutant haplotype pfdhfr/pfdhps-CIRNI/ISGEAA, associated with high-level resistance to SP, was rare (9%) among 1999 isolates and absent among 2007 isolates. Conclusions The prevalence of pfcrt and pfmdr1 alleles reported in this study is consistent with a parasite population under sustained CQ drug pressure. The low prevalence of dhps-437G and dhps-540E mutations (ISGEAA) and the rarity of quintuple-mutant haplotype pfdhfr/pfdhps-CIRNI/ISGEAA suggest that SP retains some efficacy in Swaziland. Anti-malarial policy changes in neighbouring countries may have had an impact on the prevalence of molecular markers of anti-malarial resistance in Swaziland, and it is hoped that this new information will add to understanding of the regional anti-malarial resistance map.